Decline in allogeneic blood transfusion usage in total hip arthroplasty patients: National Inpatient Sample 2009 to 2013. Issue 4 (July 2018) - Gwam, Chukwuweike U.; Mistry, Jaydev B.; Etcheson, Jennifer I.; George, Nicole E.; Connors, Grayson; Thomas, Melbin; Adamu, Hephzibah; Patel, Nirav G.; Delanois, Ronald E.
Introduction: Although total hip arthroplasty (THA) is an effective treatment for end-stage arthritis, it is also associated with substantial blood loss that may require allogeneic blood transfusion. However, these transfusions may increase the risk of certain complications. The purpose of our study is to evaluate: (i) the incidence/trends of allogeneic blood transfusion; (ii) the associated risk factors and adverse events; and (iii) the discharge disposition, length of stay (LOS), and costs for these patients between 2009 and 2013. Methods: The National Inpatient Sample database was used to identify 1, 542, 366 primary THAs performed between 2009 and 2013. Patients were stratified based on demographics, economic data, hospital characteristics, comorbidities, and whether or not allogeneic transfusion was received. Logistic regression was performed to evaluate the risk factors for transfusion and postoperative complications. Results: From 2009 to 2013, allogeneic transfusions were used in 16.9% of primary THAs, with a declining annual incidence. Except for obesity, all comorbidities were associated with increased likelihood of receiving a transfusion. Allogeneic transfusion patients were more likely to experience surgical site infections or pulmonary complications (p<0.001 for all). These patients were more likely to be discharged to a short-term care facility (p<0.001). Additionally, they had a greater mean LOS (p<0.001) and higher median hospital costs and charges when compared to their non-transfused counterparts. Conclusions: While the observed decline in allogeneic transfusion usage is encouraging, further efforts should focus on preoperative patient optimisation. Given the projected increase in demand for primary THAs, orthopaedic surgeons must be familiar with safe and effective blood conservation protocols.